KERAMIK PADA GUA DAN CERUK JABALNUR DI DESA JABALNUR KECAMATAN KODEOHA KABUPATEN KOLAKA UTARA PROVINSI SULAWESI TENGGARA - Wulandari Wulandari; Sitti Kasmiati; Abdul Alim (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
Situs Gua Jabalnur is a burial site that contains various archaeological remains still discoverable today, one of which is ceramics. The motivation behind this research was to understand the forms and methods of ceramic production found at the site. This exploration utilized essential ideas, particularly those related to ceramics, fired components, and specificity. Employing inductive/qualitative reasoning, this descriptive-analytical study collected data through literature reviews, field observations, interviews, and documentation. Morphological, technological, and stylistic analyses were used to examine the information gathered. The exploration results revealed that out of 200 tests conducted, only 27 ceramic fragments could be reconstructed, yielding 14 rim fragments, 11 body fragments, and 2 base fragments. The types of ceramics identified included bowls, pots, and plates. Among these fragments, two types of ceramics were found: porcelain and earthenware pottery. The varieties of pottery production traced at the Gua and Ceruk Jabalnur sites showed that there were 14 rim compartments consisting of 3 variants, 11 body compartments consisting of 2 variants, and 2 foot bases consisting of 2 variants. Bowls, pots, and plates were the most commonly found structures, indicating their association with everyday use. Two ceramic production techniques were identified at Gua Jabalnur: the wheel-throwing technique and surface-finishing techniques, which included brushing and dipping. The decorative motifs on the ceramics were divided into two categories: floral and faunal motifs. Additionally, five decorative techniques were identified: incising, painting, appliqué, pressing, and a combination technique involving both pressing and incising.